Case report: Canine distemper virus infection as a cause of central nervous system disease in a Eurasian lynx (Lynx lynx) - Lombardo, Mara Sophie; Mirolo, Monica; Brandes, Florian; Osterhaus, Albert D. M. E.; Schütte, Karolin; Ludlow, Martin; Barkhoff, Michael; Baumgärtner, Wolfgang; Puff, Christina (Frontiers in Veterinary Science, 2023)
The Eurasian lynx (Lynx lynx) represents an endangered species with only small populations remaining in Central Europe. Knowledge about the threat posed by potential infectious agents to these animals is crucial for informing ongoing protection measures. Canine distemper virus (CDV) is known to have a wide host range with infection reported in many mammalian species including several lynx species (Lynx pardinus, Lynx canadensis, Lynx rufus), but is an extremely rare finding in the Eurasian lynx. The present report describes a case of a Eurasian lynx showing central nervous signs, including apathy and ataxia. A CT scan revealed multiple hypodense areas in different localizations within the brain as well as enlarged liquid filled areas, leading to the suspicion of a degenerative process. Due to clinical deterioration, the animal was euthanized and submitted for macroscopical and histological investigations. Histological investigations revealed multifocal demyelinations in the cerebellum, brain stem and cervical spinal cord as well as a multifocal, perivascular, lymphohistiocytic meningoencephalitis. A CDV infection was confirmed by immunohistochemistry and RT-PCR analyses. This CDV infection of a Eurasian lynx resembles a classical chronic manifestation of distemper in dogs and highlights the threat posed by canine distemper to this species.